0075 Neural Correlates of Cognitive Fatigue in Parkinson Disease. (27th May 2020) - Liu, W; Bhavsar, R; Mamikonyan, E; Yang, F N; Lei, H; Weintraub, D; Detre, J A; Rao, H
Abstract: Introduction: Parkinson's disease (PD) is a common neurodegenerative disease affecting millions of people world-wide. Fatigue is a prevalent and debilitating non-motor symptom in PD. However, the neural correlates underlying cognitive fatigue are poorly understood. Our previous studies suggested that continuous performance of a simple but mentally demanding psychomotor vigilance task (PVT) induced cognitive fatigue, operationalized as subjective exhaustion and time-on-task performance decline. Here we used arterial spin labeling (ASL) perfusion fMRI to investigate regional cerebral blood flow (CBF) changes in PD patients during cognitive fatigue induced by continuous performance of 20-min PVT. Methods: Twenty-one PD patients completed a 20-min PVT during the ASL scan and two additional 4-min resting-state ASL scans before and after PVT. Reaction times (RTs) and regional CBF changes throughout the PVT as well as during pre- and post-task resting baselines were measured. Cognitive fatigue was analyzed by dividing the entire PVT performance into five quintiles in addition to the immediate measurement of self-rated fatigue before and after PVT. Results: PD patients demonstrated significantly increased self-reported fatigue ratings after the task (p < 0.05) and progressively slower RTs across quintiles (p < 0.05). Perfusion data showed that the PVT activates the right middle frontal cortex, right inferior parietal lobe, right insula, bilateral occipital cortex, and right cerebellum (FDR corrected). Moreover, the bilateral middle frontal gyri were less active during the post-task rest compared to the pre-task rest. Conclusion: These results demonstrated that cognitive fatigue has an ongoing effect on brain activity after a period of continuous mental effort and supported the critical role of prefrontal cortex in mediating cognitive fatigue in PD. The findings also suggest the utility of continuous PVT as an appropriate paradigm to induce and examine cognitive fatigue in PD. Support: Supported in part by Parkinson's Foundation Translational Research Grant and NIH grants R01-MH107571, R21-AG051981, and P30-NS045839.